2007
DOI: 10.1007/s11060-007-9469-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of brain metastases from breast cancer

Abstract: The prognoses for patients with brain metastases from breast cancer were generally poor, although selected patients may survive longer with intensive brain tumor treatment, such as surgical resection and/or systemic chemotherapy in addition to brain radiotherapy. For patients with unfavorable prognoses, palliative radiotherapy was effective in improving the quality of the remaining lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 33 publications
4
46
1
1
Order By: Relevance
“…In comparison to other data in the literature, this interval is slightly shorter; median survival times between 4.5 and 10 months have been reported (12)(13)(14)(15)(16).…”
Section: Discussioncontrasting
confidence: 50%
“…In comparison to other data in the literature, this interval is slightly shorter; median survival times between 4.5 and 10 months have been reported (12)(13)(14)(15)(16).…”
Section: Discussioncontrasting
confidence: 50%
“…Although there have been conflicting findings, numerous variables have been shown to have some prognostic value including the following: Basal subtype (20,21,51); whole brain radiation dose of greater than or equal to 30 Gy (20,22); KPS (19,(22)(23)(24)(25)(26)(27)(28)(29)(30); presence/degree of extracranial metastases (21-23,27,30,31); primary tumor control (24,32); size of primary tumor (22); interval from first cancer diagnosis to brain metastases (23); number of brain metastases (22,23,32,33); solitary metastasis (22,34); age (19,21,24,30,34); ER status (21,24,26); HER2 expression (22,24,29,30,32,35); systemic chemotherapy (28); lymphopenia (29,36); and surgical resection (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated tumor subtype affects prognoses (16)(17)(18), however, neither the RTOG-RPA classification system nor the current Breast-Specific GPA system include tumor subtype in their models. Many other authors have described other prognostic factors, albeit with conflicting findings (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Gaspar et al published a seminal work on a prognostic index for patients with brain metastases, the Radiation Therapy Oncology Group's Recursive Partitioning Analysis (RTOG-RPA) in 1997 (38).…”
Section: Introductionmentioning
confidence: 99%
“…Una calificación en Karnofsky ≤70 al diagnóstico, por ejemplo, se ha asociado con un mayor riesgo de muerte por metástasis al SNC. 8,11,15,24 Los resultados del presente estudio son similares a los datos publicados previamente por Anders y colaboradores 25 pues, según los resultados de su trabajo, las metástasis al SNC se presentan principalmente en mujeres que fueron diagnosticadas en etapas localmente avanzadas y con subtipos luminal y TN. En ese mismo trabajo, el tratamiento con QT fue administrado a 89% de las pacientes, en comparación con 99% de este estudio.…”
Section: Discussionunclassified